Characterization and Atmospheric Drivers of Nocturnal Ozone Enhancement in Putian City, China - Chunsheng Fang; Xiaowei Zhou; Yuxuan Cai; Ju Wang (Atmosphere)
The increasingly severe nocturnal ozone enhancement (NOE) event pollution is widely concerning. Therefore, based on the observed hourly O3 concentrations from 2015 to 2023, this study analyzes the characteristics of NOE events over Putian City. The analysis results show that the frequency of NOE events over Putian City is high, at about 127 days annually, with a high frequency in April and a low frequency in July and August. Most NOE events corresponded to a nocturnal O3 peak concentration (NOP) of <120 μg/m3. Moreover, they mainly occurred between 1:00–3:00 and 7:00. The physicochemical processes over Putian City in April, October, and November 2020 were simulated using the Weather Research and Forecasting (WRF, version 4.3.3) model coupled with the Community Multiscale Air Quality (CMAQ, version 5.4) model. The results suggest that O3 transport, especially horizontal transport from the eastern sea and Zhejiang Province and vertical transport from the upper atmosphere, could be the major cause of NOE events over Putian City. Furthermore, the nocturnal movement of the pollution zone, along with the aggregation of O3 due to weakened dry deposition and the influence of a stable boundary layer obstructed by mountain terrain, significantly influenced the overall O3 concentration. Thus, NOE events over Putian City stem from the interaction among these physicochemical processes. The study results emphasize the importance of O3 control in Putian City and suggest the implementation of strict joint regional control measures for to improve air quality.